Legal Protection of Women as Victims of Sexual Harassment Through Electronic Media in Indonesia's Positive Law - Nur Tania Bakhti; Neni Vesna Madjid; Fahmiron (Ekasakti Journal of Law and Justice, 2025)
Sexual harassment through electronic media is one of the human rights violations. The crime of sexual harassment through electronic media is regulated in existing laws and regulations in Indonesia, such as Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, Law Number 44 of 2008 concerning Pornography, and Law Number 12 of 2022 concerning the Crime of Sexual Violence. The approach used is Normative Juridical. The position of women as victims of sexual harassment through electronic media is that women are objects or victims who receive sexual harassment through electronic media, because women are always considered weak and easier to get harassment treatment. Legal protection for women as victims of sexual harassment through electronic media according to positive laws in Indonesia, namely, still has shortcomings and can even ensnare victims into perpetrators.